Corporate governance and performance: evidence from an emerging market / Siti Nuryanah and Sardar M. N. Islam. - Siti, Nuryanah; Islam, Sardar M. N. (Universiti Teknologi MARA Cawangan Selangor, 2011)
This study investigated the relationships between the internal corporate governance mechanisms and firm performance in Indonesia. Recognising weak external mechanisms of Indonesian corporate governance, this study focused on the internal mechanisms, hence offering considerable insights for the understanding of the relationships between internal corporate governance mechanisms and performance in Indonesia. The main proposition of this study was that the traditional findings on the relationships between internal corporate governance mechanisms and company performance relevant to developed countries were not appropriate for emerging markets like Indonesia where the business environment is different as, for example, the capital market is still under-developed, and the regulatory framework is weak. Using a panel data during 2002-2004, the findings show that all internal mechanisms except size of both board and audit committee, and management ownership are significant in explaining company performance. Specifically, some results on the audit committee are different to the literature of best practice of audit committee. The findings, therefore, support our proposition that the role of some specific aspects of internal corporate governance mechanisms affecting company performance does not exist in Indonesia.